Hak kebebasan berpendapat di media sosial perspektif Hak Asasi Manusia - Maula, Syahrina Rafa (Maliki Interdisciplinary Journal, 2026)
Freedom to express ideas is recognized as one of the essential human rights that supports the existence of a democratic society. In today’s digital era, social networking platforms have transformed into widely used spaces where people can communicate thoughts, deliver criticism, and share public aspirations openly with broader audiences. Within Indonesia, the right to voice opinions has received legal recognition and protection through existing regulations. At the same time, technological advancement in social media has significantly changed the way opinions are delivered, allowing information and viewpoints to spread more rapidly and reach larger communities in a short period of time. Even so, the exercise of this freedom cannot be carried out carelessly. Every individual is still expected to respect ethical standards, cultural values, and legal provisions so that their expressions do not create negative impacts or violate the rights of others. For this reason, using social media as a channel for public expression requires both maturity and accountability. By maintaining a balance between personal freedom and social responsibility, people can exercise their right to speak in a constructive manner while still upholding democratic values and respect for human rights.